EKSPERIMENTASI MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) DAN LEARNING CYCLE 5E (LC5E) PADA MATERI TRIGONOMETRI DITINJAU DARI AKTIVITAS BELAJAR SISWA SMA/MA NEGERI DI KABUPATEN KARANGANYAR - Nurcahyo, Andriawan; Sujadi, Imam; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of research was to determine the effect of learning models onÂ  learning achievement viewed from the students learning activities. The learning models compared were two stray two stay (TSTS), learning cycle 5E (LC5E) and direct learning. This research method was quasi â experimental using the factorial design 3x3. The Population of this research was all students in the tenth grade of High School / MA in Karanganyar in the academic year of 2013/2014. The Sampling was done by stratified cluster random sampling. The total samples in this research were 340 students (113 students for TSTS class, 113 students for LC5E class and 114 students for direct learning model). The proposed hypothesis of the research were tested by using the two-way analysis of variance with unbalanced cells. The conclusions of this research were as follow: (1) cooperative learning model TSTS, LC5E and direct learning model have the same achievement inÂ  trigonometry. (2) students having high learning activities of mathematics study have the same achievement with those having medium learning activities, students having high learning activities of mathematics have better achievement than those having low learning activities, and students having medium learning activities have the same achievement with those having low learning activities in the trigonometry. (3) In the category of learning activities, students having high, medium and low, learning model TSTS, LC5E and direct learning model, have the same achievement in trigonometry. (4) In the learning modelÂ  TSTS and LC5E, students having high, medium and low learning activities have the same achievement trigonometry. For direct learning model, students having high learning activities have the same achievement with those having low learning actvities, students having high learning activities have better achievement than those having low learning activities, and students having medium learning activities have the same achievement with those having low learning activities.Keywords: TSTS, LC5E, Students Learning Activities and Learning AchievementÂ Â